Impactos e danos ambientais na mineração: diferenciação conceitual e instrumentos de controle para efetivação da tutela do meio ambiente - Brito, Luis Antonio Gomes de Souza Monteiro de (2019)
This research analyze the conceptual distinction between negative environmental impact and environmental damage to identify a possible practical relevancy of that differentiation on the use of juridical instruments of prevention, control and repair of negative environmental harms caused by mining activities. The main intention was to ensure that instruments eventually designed to control one category were not improperly applied to the other, as is usually happens in practice, including by the Courts and much motivated by a confusion made by the specialized doctrine. As result, it has been show that environmental impact and environmental damage, although may even be visually identical, are legally differentiated in relation to the moment of occurrence, origin, predictability, tolerability and the legal instrument of control, even in an economically strategic and necessarily impacting business such as mining. From this, in order to confirm the conclusion of the thesis, the research showed that instruments such as environmental licensing and studies, administrative compensatory measures and mining royalties represent measures of environmental impacts control that must be prevented, mitigated or compensated. In the same way, also to confirm the result obtained in the research, it was shown that civil, administrative and criminal liabilities represent legal reactions to environmental damage, not to environmental impact, and that the reparation of harms is the priority strategy in relation to the punishment of the offender, a composition that is made prevalently by environmental civil liability, but that can be carried out by other systems of liability as an absolute or partial alternative to administrative and penal punishments